REPRESENTATION DISCRIMINATION OF WOMAN ROLE IN DOCUMENTARY FILM “SURGA KECIL DI BONDOWOSO” (SEMIOTIC ANALYSIS BY ROLAND BARTHES) - Anastasya, Selaya; Sunarto, Sunarto; Bayu Widagdo, Muhammad (Interaksi Online, 2024)
The documentary film "Surga Keci di Bondowoso" aims to advocate gender equality by depicting the involvement of a husband in household affairs and the wife's role as the breadwinner. However, forms of role discrimination against women are still prevalent. Therefore, the primary objective of this research is to analyze and describe the forms of discrimination against women's roles and examine the dominant ideology within the text. The research method employed is descriptive qualitative using Roland Barthes' semiotic analysis model (5 codes). The main theories utilized are the standpoint theory, supported by liberal feminist theory. To identify forms of discrimination against women's roles in 5 selected scenes, indicators of gender discrimination by Fakih are applied, including marginalization, subordination, stereotypes, violence, and double duties. Data collection techniques involve documentation and literature review through relevant books and journals. The research findings reveal the persistence of the dominant patriarchal ideology, which discriminates against women's roles both in public and domestic spheres, manifested through marginalization, subordination, and stereotypes, ultimately portraying wives as domestic actors and housekeepers. Discrimination in women's roles is mostly carried out by individuals, with the majority of gender being women. The discovery suggests that as a gender equality-based documentary, there should be no forms of discrimination against women's roles, particularly depicting career wives as powerless within the household. Critically, the research findings indicate that it is inappropriate for the content of the film to be used as a reflection of gender equality, as masculine glorification is still evident in this documentary. Overall, the research underscores the need for more accurate and unbiased representations of gender roles in documentary films, fostering genuine gender equality and eliminating patriarchal biases.